Analisis Tinjauan Ekonomi Teknis dalam Pemasangan Kapasitor Bank untuk Memperbaiki Nilai Faktor Daya pada Beban Industri - Samuel Kristiyana; Muhammad Suyanto; Maulana Maliq F; Diky Rahmadi; Prastyono Eko Pambudi (Institut Teknologi Dirgantara Adisutjipto, 2022)
Industry is one of the largest users of reactive power in the distribution of electric power. Industries use equipment such as induction motors, transformers and other equipment to support their production needs. Loads such as induction motors are inductive loads that require reactive power to operate. Reactive power in an electric power distribution network is a loss. Reactive power can reduce the effectiveness of the real power which is converted into active power so that the efficiency of real power usage is reduced. Installing a capacitor bank is one way to compensate for the use of reactive power in a load. Installing capacitor banks aims to improve the value of the power factor that has decreased due to the use of excessive reactive power loads. PLN has set a standard power factor value for consumers of 0.85 and reactive power consumption of 0.62 of the total power consumption. For this reason, it is necessary to carry out further analysis regarding the advantages and disadvantages of installing bank capacitors to improve the value of the power factor so that the ideal economic factor for consumers is obtained.